Preference Heterogeneity in Contingent Behaviour Travel Cost Models with On-site Samples: A Random Parameter vs. a Latent Class Approach - Hynes, S.; Greene, William (Wiley-Blackwell, 2016)
In this paper, we examine heterogeneity in the trip preferences of recreationists. We apply a random parameters negative binomial model and a latent class negative binomial model to a panel dataset of beach users at a site on the west coast of Ireland, where access across farmland has been restricted. This approach allows us to account for heterogeneity with respect to the impact of the chosen explanatory variables in a contingent behaviour travel cost model of demand where the researcher must also account for the fact that the sample data has been collected on-site. The analysis also develops individual consumer surplus estimates and finds that estimates are systematically affected by both the random parameter and latent class specifications. There is also evidence that accounting for individual heterogeneity improves the statistical fit of the models and provides a more informative description of the drivers of recreationalist trip behaviour.